Han-Wei Liu & Weiping He Australian Banking and Finance Law and Regulation - Leow, Bryan; Lau, Kwan Ho (Faculty of Law, Universitas Brawijaya, 2025)
It is a near-Sisyphean feat to properly set out the myriad interlinking issues in banking and finance law within a jurisdiction, and this is before tackling the accompanying regulatory issues. Pushing that proverbial boulder up the hill requires a firm grounding in the applicable black-letter rules; a good sense of the regulatory theories adopted by the supervisory authorities; and, finally, a keen appreciation of potential problems presented by the constant stream of novel financial products (and technology). In their book Australian Banking and Finance Law and Regulation, Han-Wei Liu and Weiping He have examined the Australian position relating to the above in a comprehensive and easily digestible volume.